?ENVIRONMENTAL ADAPTATION ANALYSIS OF SEVERAL UPLAND COTTON VARIETIES (Biological Sciences - PJSIR, 1997)
Ten Pakistani upland cotton varieties, all hirsutum types were collated for their environmental adaptation in three sites over three years for seedcotton yield, lint % and fibre length. Stability parameters considered in this study were, regression coefficient (b), deviations from the regression line (S2-d),mean over environments and coefficient of variability (CV). Ina combined analysisof variance, varietyx environment interaction factor was recorded signifi- cant for all the traits that allowed further partitioning of this factor into environment linear, variety x environment linear and pooled deviations from the regression. Environment linear and variety x environment linear were also significant for all the traits, connoted genetic differences among the varieties for their response to varying environ- ments. Varieties Sarmast and NIAB-78 were comparatively more stable to variable environments for seedcotton yield, CRIS-9 and NIAB-78 for lint % and Qalandri, Shaheen, CIM-70 and CIM-109 for fibre length due to their means higher than the grand mean, regression coefficients equal or close to unit slope and smaller deviations from the regression line for respective traits. Whereas under specific environments of favourable nature, varieties CRIS- 9, Shaheen and CIM-109 would be desirable for seedcotton yield and Shaheen, CIM-70 and MNH-93 for lint % and K-68-9 for fibre length. For less favourable environments, varieties Qalandri, Rehmani and ClM-70 would perform better for yield, Qalandri and K-68-9 for lint % and CRIS-9 for fibre length.